(untitled) (TAJ: Journal of Teachers Association, 2009)
Parkinson’s disease is a common disease of old age, whose major symptoms are of motor nature. Apart from the symptoms related to motor activity, patients of PD also experience various other fluctuating symptoms of a non-motor nature. These non-motor fluctuations (NMF) have been classified according to their characteristics into three categories; dysautonomic, mental (cognitive / psychiatric), and sensory / pain. These non-motor fluctuations may have a varied presentation and unless recognized by the physicians to be a feature of PD itself, lead to unnecessary and often costly or harmful investigations. The varied presentations of the non-motor fluctuations in patients of PD are presented in this study. 128 patients of PD from the Movement Disorder Clinic of the Neurology Out Patient Department of BSMMU were included in this study. 106 had motor fluctuations and 111 had non-motor fluctuations. The non-motor fluctuations were classified into sensory in 67 (63.2%) patients, autonomic in 78 (73.6%) patients and psychiatric in 18 (17%) patients. The most frequent sensory fluctuations were akathisia, pain and tingling sensations. Excessive sweating, drooling, oral dryness and flushing were the common autonomic fluctuations while depression and fatigue were the common psychiatric complaints. Most of the non-motor fluctuations were associated with motor fluctuations and with the "off" state. doi: 10.3329/taj.v20i2.3071 TAJ 2007; 20(2): 116-121